Perda auditiva neurossensorial súbita idiopática: pesquisa de citocinas inflamatórias (Tnf-Alfa E Il-6) em cultura de células mononucleares periféricas - Tincani, Stefano [UNIFESP] (2017)
Objective: Analyze production of Tumor Necrosis Factor-alpha (TNF-α) and Interleukin-6 (IL-6) in peripheral mononuclear cells of patients with Idiopathic Sudden Sensorineural Hearing Loss (ISSNHL). Method: Case-control study with patients presenting with ISSNHL seen from August 2013 to March 2015 followed by the clinic of the Department of Otorhinolaryngology and Head and Neck Surgery, Paulista School of Medicine/ Federal University of São Paulo. Audiometric parameters were analyzed before and after treatment, at least 30 days after hearing stabilization or treatment ending. Blood samples were collected to perform peripheral blood mononuclear cell culture and analyze TNF-α and IL-6 production. The samples were divided in to two culture plates, one of which had lipopolysaccharide (LPS) added as inflammatory stimulus. Results: Production of both cytokines was reduced with or without LPS stimulus in the case group when compared to the control group. Thirty-one patients with ISSNHL passed inclusion and exclusion criteria for the study group, of which 17 were female and 13 male. Average age was 47.1 years, with a median of 44.5 years. Minimum age was 16 and maximum 76 years. The control group was composed of 39 people, 24 female and 15 male. Average age was 49 years, median 46 years, minimum of 16 and maximum of 86 years. Comorbid diseases played no role in severity of illness of prognosis. Conclusion: Inflammatory activation is diminished in the peripheral blood mononuclear cells of patients with ISSNHL in relation to healthy individuals.